Analisis Zat Pemanis Sakarin dan Siklamat Pada Minuman Bubble Drink yang Dijual di Kota Surakarta - Wimpy; Harningsih, Tri; Siska Wardani, Tatiana (Jurnal Farmasi (Journal of Pharmacy), 2020)
Sweetener known as a compound that is intentionally added and used to improve it’s taste and aroma,it also used to improve physical and chemical properties. It also used as the source of calories for the body. There are two types of sweetener : natural sweeteners and artificial sweeteners. Beverage and food producers such as bubble drink producer prefer to use artificial sweeteners rather than natural sweeteners because it is cheaper and sweeter than natural sweeteners. If we use excessive amounts of saccharin and cyclamate, they can lead to many health problems such as neurological diseases, hypertension, and brain cancer.This is an experimental research with purposive sampling method. Samples were collected from bubble drink sellers in 5 sub-districts of the Surakarta City. The experiment was conducted at the National STIKES Chemistry Laboratory. Saccharin and cyclamate were determined by rapid test kits. Qualitative test results on 25 buble drinks did not show the presence of saccharin and cyclamate sweetener.